PENDIDIKAN EKSTRAKURIKULER BALAI LATIHAN KERJA (BLK) KEDUNGADEM BOJONEGORO DALAM MENGASAH KETERAMPILAN KERJA DAN KREATIVITAS SISWA - Huda, Nur; Kibtiyah, Asriana (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2024)
Extracurricular education at BLK Madrasah Aliyah Sunan Drajat Kedungadem Bojonegoro provides knowledge, skills and work creativity. This is part of non-formal education that complements formal education to develop students' potential. This research aims to understand how BLK sharpens students' work skills and creativity, as well as identifying factors that support and hinder the role of BLK extracurricular activities in developing students' work skills and creativity. This research is a field case study conducted at BLK Madrasah Aliyah Sunan Drajat Kedungadem Bojonegoro. Descriptive research methods are used to explain the situation in the field thoroughly, broadly and in depth. The results of this research show that the BLK extracurricular program at Madrasah Aliyah Sunan Drajat Kedungadem plays an important role in honing students' work skills and creativity. Through banner design training, this program provides opportunities for students to develop their interests and talents, as well as supporting extracurricular activities. It is hoped that this program can produce students who are reliable and professional in the field of design. However, there are obstacles in mastering the Photoshop program tools and limited training time. To overcome these obstacles, the instructor has used an LCD projector and applied practical theory so that participants can understand the material better.